Cultural Imperialism and Popular Culture: Unveiling the Influence of Salmah Ismail @ Saloma in the Federation of Malaya - Mohd Amir Mohd Zahari, Mardiana Ismail (Tanjung Malim, 2024)
Cultural Imperialism and Popular Culture: Unveiling the Influence of Salmah Ismail @ Saloma in the Federation of Malaya by Mohd Amir Mohd Zahari, Mardiana Ismail